Impact of Different Sampling Schemes for Decision Making in Soil-Transmitted Helminthiasis Control Programs. (12th December 2019) - Coffeng, Luc E; Malizia, Veronica; Vegvari, Carolin; Cools, Piet; Halliday, Katherine E; Levecke, Bruno; Mekonnen, Zeleke; Gichuki, Paul M; Sayasone, Somphou; Sarkar, Rajiv; Shaali, Ame; Vlaminck, Johnny; et al.
Abstract: Starting and stopping preventive chemotherapy (PC) for soil-transmitted helminthiasis is typically based on the prevalence of infection as measured by Kato-Katz (KK) fecal smears. Kato-Katz-based egg counts can vary highly over repeated stool samples and smears. Consequentially, the sensitivity of KK-based surveys depends on the number of stool samples per person and the number of smears per sample. Given finite resources, collecting multiple samples and/or smears means screening fewer individuals, thereby lowering the statistical precision of prevalence estimates. Using population-level data from various epidemiological settings, we assessed the performance of different sampling schemes executed within the confines of the same budget. We recommend the use of single-slide KK for determining prevalence of moderate-to-heavy intensity infection and policy decisions for starting and continuing PC; more sensitive sampling schemes may be required for policy decisions involving stopping PC. Our findings highlight that guidelines should include specific guidance on sampling schemes.